Facilitating attitudinal learning in an animal behaviour and welfare MOOC. (2nd September 2017) - Watson, Sunnie Lee
ABSTRACT: This case study examines the design and facilitation of a Massive Open Online Course (MOOC) that focused on attitudinal learning about the topic of animal behaviour and welfare. Findings showed that a team of instructors worked together collaboratively towards realising learning goals and found the experience rewarding. While learners had mixed perceptions of gains in cognitive, affective and behavioural learning, they reported high satisfaction with lecture videos and instructor course participation. Implications for the instructional design of MOOCs and attitudinal learning are discussed based on these findings, including a discussion of MOOCs as a unique platform for attitudinal learning, and recommendations for their successful use. The recommendations include the importance of creating a collaborative instructor team, establishing high instructor presence, using interactive and collaborative learning activities, and receiving support from platform providers and institutions.